2015
DOI: 10.1038/srep15697
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcing endothelial junctions prevents microvessel permeability increase and tumor cell adhesion in microvessels in vivo

Abstract: Tumor cell adhesion to the microvessel wall is a critical step during tumor metastasis. Vascular endothelial growth factor (VEGF), a secretion of tumor cells, can increase microvessel permeability and tumor cell adhesion in the microvessel. To test the hypothesis that inhibiting permeability increase can reduce tumor cell adhesion, we used in vivo fluorescence microscopy to measure both microvessel permeability and adhesion rates of human mammary carcinoma MDA-MB-231 cells in post-capillary venules of rat mese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 61 publications
(118 reference statements)
3
30
0
Order By: Relevance
“…Tumor cells which enter the circulation must attach to the vascular wall and extravasate through the impermeable barrier presented by normal endothelium in order for metastasis to proceed . The vital importance of the barriers to metastasis present at the stage of extravasation is reflected in the observation that only a tiny minority of circulating cancer cells (<0.01%) successfully establish secondary tumors . Therefore, therapeutic strategies which directly enhance the activity of these physiological barriers to tumor cell extravasation would be predicted to attenuate cancer metastasis …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tumor cells which enter the circulation must attach to the vascular wall and extravasate through the impermeable barrier presented by normal endothelium in order for metastasis to proceed . The vital importance of the barriers to metastasis present at the stage of extravasation is reflected in the observation that only a tiny minority of circulating cancer cells (<0.01%) successfully establish secondary tumors . Therefore, therapeutic strategies which directly enhance the activity of these physiological barriers to tumor cell extravasation would be predicted to attenuate cancer metastasis …”
Section: Discussionmentioning
confidence: 99%
“…One of the key events in the progression of cancer metastasis is the migration of circulating tumor cells through vascular endothelium . Tumors induce abnormal endothelial permeability by various mechanisms in order to promote this process of cancer cell invasion and recently inhibition of tumor‐induced vascular permeability has been shown to attenuate metastasis in vivo …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to step out of the flow, a very important step is the so called “adhesion cascade” (Guo et al 2004; Haier and Nicolson 2001; Stroka and Konstantopoulos 2014; Wirtz et al 2011). Most previous studies have experimentally (Cheung et al 2011; Fu et al 2015; Guo et al 2014; Yan et al 2012; Zhang et al 2016) and numerically (Rejniak 2012; Yan et al 2012; Yan et al 2010) investigated the process of cell adhesion to the blood vessel. The numerical studies simply regarded the blood as a homogenous Newtonian fluid (Rejniak 2012; Yan et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have demonstrated that the increase of intracellular cAMP by an adenylyl cyclase (AC) activator, forskolin, or cAMP analogs attenuates acute permeability responses of cultured ECs to platelet-activating factor or thrombin (16). It has also been shown that cAMP reduces VEGF-induced permeability in intact microvessels (17). The observed endothelial barrier stabilization by cAMP is generally attributed to the effects of cAMP on cell contractility and stability of tight/adherens junctions (18, 19).…”
mentioning
confidence: 99%